Influence of a Large-Eddy-Breakup-Device on the Turbulent Interface of Boundary Layers - Chin, Cheng; Orlu, Ramis; Schlatter, Philipp; Monty, Jason; Hutchins, Nicholas (Flow Turbulence and Combustion, 2017)
The effects of implementing a large-eddy break-up device (LEBU) in a turbulent boundary layer on the interaction with the boundary layer is investigated with particular emphasis on the turbulent/non-turbulent interface (TNTI). The simulation data is taken from a recent well-resolved large eddy simulation (Chin et al. Flow Turb. Combust. 98, 445–460 2017), where the LEBU was implemented at a wall-normal distance of 0.8 δ (local boundary layer thickness) from the wall. A comparison of the TNTI statistics is performed between a zero-pressure-gradient boundary layer with and without the LEBU. The LEBU is found to delay the growth of the turbulent boundary layer and also attenuates the fluctuations of the TNTI. The LEBU appears to alter the structure size at the interface, resulting in a narrower and shorter dominant structure (in an average sense). Further analysis beneath the TNTI using two-point correlations shows that the LEBU affects the turbulent structures in excess of 100 δ downstream of the LEBU.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Large eddy simulation; Large-eddy-break-up device; Turbulent/non-turbulent interface; Wall-bounded turbulence